Resilience in COVID-19: holistic thinking, meaning-making, and positive reappraisal - Nah, Hilda (Nanyang Technological University, 2023)
The present research examined the role of holistic thinking, meaning-making, and positive reframing, on resilience in the COVID-19 pandemic. Past work has reported that holistic thinking, meaning-making, and positive reframing buffer against life stressors. However, little to no research have explored direct links between the constructs on resilience. As a relatively novel topic, the present research aimed to investigate causal relationships between holistic thinking, meaning-making, and positive reframing on resilience, in the context of the COVID-19 pandemic. Hence, we hypothesised that (i) holistic thinking increases one’s tendency for meaning-making, (ii) holistic thinking increases one’s tendency for positive reframing, and (iii) holistic thinking leads to stronger resilience. To test our hypotheses, 250 participants were recruited and randomly assigned to two conditions: holistic thinking or control in a between-subjects design. All participants were asked to recall their most stressful experiences in the COVID-19 pandemic. After which, they underwent image-based primes to either induce patterns of holistic thinking or serve as a control and were tasked to complete a series of questionnaires and behavioural measures. Contrary to the predictions, the present study found no statistically significant causal relationships between holistic thinking, meaning-making, positive reframing, and resilience. In contrast, the results of exploratory analyses found positive reframing as a statistically significant predictor of resilience. The paper discusses theoretical and practical implications of the relationship between holistic thinking, meaning-making, positive reframing, and resilience in the context of the COVID-19 pandemic.